Mechanical characteristics of self-compacting mortars with raw and expanded vermiculite as partial cement replacement at elevated temperatures - Benli, Ahmet; Karatas, Mehmet; Toprak, Hasan Anil (Elsevier Sci Ltd, 2020)
In this study, the effects of raw vermiculite (RVM) and expanded vermiculite (EVM) on the durability and mechanical characteristics of self-compacting mortars (SCMs) at ambient and elevated temperature were investigated. In this context, nine SCMs series were designed by substituting of RVM and EVM at the rates of 0%, 5%, 10%, 15% and 20% as mineral additives on weight basis including the control mix. A total of 81beams of 40x40x160 mm size were cast and left water curing for the age of 3, 28 and 90 days for measuring strength properties. 54 cubes of 50x50x50 mm size were cast and left water curing for the age of 28 and 90 days to measure durability characteristics such as porosity, water absorption, sorptivity and density of SCMs. To measure the fresh characteristics of SCMs, slump diameter and mini V-funnel flow tests were assessed. The rheology of SCMs was determined by performing the viscosity test. The hardened SCMs specimens cured at 28 days were exposed to 300, 600 and 900 degrees C respectively. The experimental results pointed out that as the content of RVM and EVM enhances, a remarkable reduction in compressive and flexural strength of SCMs specimens was seen at all water curing ages at ambient temperature. Flexural strength of RVM20 at 90 days exhibited very small decline compared to 28 days flexural strength. The results exhibited that EVM specimens showed more high temperature resistance than RVM specimens. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: High Temperature; Self-Compacting Mortars; Expanded vermiculite; Raw Vermiculite; Mechanical Properties; Transport Properties